KINERJA PEGAWAI BALAI KESEHATAN WENAM DISTRIK PRIME KABUPATEN LANNY JAYA - WENDA, ETINUS; PLANGITEN, NOVVA; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2017)
ABSTRAKThe objective of this study is aimed at fiding out the performance of civil servants/employees of the medical clinic atwenam district, lanny jaya regency, in providing services to community/ society.This study is conducted using qualitative method. The informants involved in this study are: 4 civil servants/ employeesof wenam medical clinic. (1. Person who is in charge, 2. Nurses and I midwife), and 2 (two) resindents of wenam village. Thedata collection and interview technique. The analysis used is the interactive model by miles and hu berman.Based on the findings of the data analysis, it is concluded that the performance of the employees at wenam medicalclinic is still not good or low viewed from: 1.The quality providing healthcare service to community, of work (exactness, spacd,and accuracy in providing healthcare service to community, 2. Quantity of work/ the execution of healthcare service tocommunity. 3. The use of working hours (absences, slowness, the lost of effective working hours), and 4. The conaboration withco-worker in carrying out the job of healthcare service to community.Based on the study,s findings it is recommended that more efforts or actions should be done to increase theperformance of employees at the wenam medical clinic amons ofhers;1. To increace the infrastructure of wenam medical clinic,Particularhy the provision of medical equipment and ofher health facilities, 2. To enhance the motivation of employees byproviding then special or additional allowances, 3. Providing the facilityof heusing to the employees of wenam medical clinicwhich is located near the clinic.Key words: Employees performance healthcare service